Pengaruh Dukungan Sosial terhadap Work Family Conflict pada Guru yang Sudah Menikah - Nuldela, Anes Julia; Erliana, Yossy Dwi; Insan, Imammul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to investigate how social support impacts work-family conflict among married teachers in Alas District, Sumbawa Regency. The research adopts a quantitative approach with a correlational design. The study's population comprised all married female teachers working at the junior/senior high school level in Alas District, Sumbawa Regency, totaling 97 individuals. The sampling method employed was total sampling, resulting in a total sample size of 97 participants. Findings indicated a significant relationship between social support and work-family conflict among married female teachers in Alas District, with a significance level of Sig. 0.000 < 0.05. Social support was found to contribute 40.9% to work-family conflict, while 59.1% was influenced by other variables.